(untitled) (Research, Society and Development, 2020)
In Brazil, the use of heat pumps in drying processes is limited to a few experimental works, with the use of imported equipment for strictly laboratory use, on very small scales. Thus, the work brings important contributions, as it provides a series of information, such as energy data, that can be used for dimensioning. In the laboratory research work on drying natural and pulped coffee at different temperatures, two systems were used: a conventional dryer with resistive heating and a prototype of a hygroscopic controller based on heat technology. The objective of this work was to determine and evaluate the consumption of electric energy, the specific rate of water removal (SMER) and the heat pump performance coefficient (COP). The SMER experimental values ​​obtained for the heat pump dryer ranged between 0.0188 and 0.1169 kg of water / kWh, whereas for the conventional dryer, these values ​​were between 0.0058 and 0.01 kg of water / kWh. The results showed that the heat pump dryer was more efficient than the conventional, sensitive heating dryer and that the SMER values ​​depend on the drying conditions and the physical characteristics of the product.